Experimental alimentary obesity in mature mat rats using the model of passive tobacco smoking - O. Yu. Mazur (Морфологія, 2020)
Background. Obesity is one of the main risk factors for a number of chronic diseases. However, the available data concerning the pathogenetic mechanisms of pathomorphological changes in lung tissue, its predominant localization, as well as a reliable list of diseases for which the overweight is considered as a risk factor, are limited and contradictory. Objective. To create a model of experimental obesity closest to human model with the simultaneous use of an experimental model of smoking to study the pathogenetic aspects of the occurrence of pathomorphological changes in the lungs. Methods. The total sample of experimental animals included 120 individuals. Subsequently, 4 groups of animals were formed by blind method: control group (C group, n =30) – with the nutrition according to the standard diet; group of rats exposed to smoking without obesity modeling (group S, n=30); group of rats with experimental obesity modeling (group O, n=30); group of rats with experimental obesity modeling tobacco smoke exposure (group OS, n=30). The groups were comparable, with no statistically significant difference (p> 0.05). Results. During the experiment, the body weight of rats of the group CL increased by 36.07 ± 2.29 g (14.77% weight gain), group S by 31.50 ± 0.92 g (13.33% weight gain), group O by 141.33 ± 3.18 g (54.65% of weight gain) and the group OS by 132.63 ± 0.45 g (52.51% of weight gain). The rats of the group OS had the highest weight gain respectively. The data obtained indicate that a high-calorie diet is a decisive factor in the development of obesity. The OS and S groups, in which the experimental model of passive smoking was used, as expected, showed lower rates of weight gain; similar results were obtained in a number of other studies: body weight and body mass index (BMI in kg / m2) were lower in smokers than in non-smokers. Conclusion. According to the obtained results, the used models were effective for the study of experimental obesity, obesity in combination with smoking and smoking alone. Therefore, these models can be considered for the study of pathogenetic mechanisms of obesity and passive tobacco smoking.